THE EFFECT OF PATIENT ACCEPTANCE THROUGH ONLINE MEDIA ON PATIENT SATISFACTION AT CICENDO EYE HOSPITAL BANDUNG - Desy Purwanti; Rosmiati Rosmiati; Farida Gustini (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine The Effect of Patient Acceptance Through Online Media on Patients at Cicendo Eye Hospital Bandung in the Covid-19 Situation. This research uses method with quantitative approach, data analysis technique: validity test, reliability test, simple linear regression test, t test and coefficient of determination test. Data collection techniques used were observation, questionnaires, literature study with the research subjects were outpatients at Cicendo Eye Hospital Bandung with simple random sampling technique as many as 30 people. The results of the study based on simple linear regression analysis found that there was no significant effect of online reservation on patient satisfaction. The positive correlation coefficient means that it has a unidirectional relationship. The better the online reservation owned by the hospital, the higher the patient satisfaction. Conversely, if the online reservation is bad, the patient satisfaction will also be low, therefore the hospital leadership, especially the Cicendo Eye Hospital Bandung, continues to provide online reservation services to patients to get increased patient satisfaction. Keywords: Online Media, Patient Satisfaction, Cicendo Eye Hospital Bandung